Oestrogen receptor β expression in pleomorphic adenomas of the parotid gland. Issue 9 (4th September 2009) - Wong, M H W; Dobbins, T A; Tseung, J; Tran, N; Lee, C S; O'Brien, C J; Clark, J; Rose, B R
Abstract : Aims: Pleomorphic adenomas of the salivary gland have gender and age distributions suggesting that oestrogen has a causal role. However, oestrogen receptor (ER)α is expressed at low levels in normal salivary gland tissues and data from salivary gland tumours are conflicting. There is preliminary evidence that the recently described ERβ may be the major ER in salivary gland tissue. The aim of this study was to determine the nature and extent of ERβ expression in pleomorphic adenomas of the salivary gland. Methods: Pleomorphic adenomas and normal tissues of the parotid gland from 49 patients were tested for ERα and ERβ expression by semiquantitative immunohistochemistry. Associations were sought with patient age and gender. Results: ERα and ERβ expression was localised mainly to the nuclei of ductal cells in normal tissues and the epithelial components in pleomorphic adenomas. Within each tissue and receptor type there were no associations between ER positivity and patient age or gender. ERβ was expressed in almost twice as many normal tissues and pleomorphic adenomas as ERα. Expression of ERβ was also significantly higher in tumour compared with normal tissues. Conclusions: This is thought to be the first study of ERβ in pleomorphic adenomas of the salivary gland. Findings support ERβ as the major ER in salivary glands, and provide evidence that ERβ may have a role in the development of pleomorphic adenomas of the salivary gland.